Emprego de oxigênio e peróxido de hidrogênio como auxiliares na decomposição de amostras biológicas por via úmida assistida por radiação micro-ondas - Bizzi, Cezar Augusto (2012)
In the present work it was investigated the possibility of using diluted HNO3 solutions for digestion of biological samples (milk powder and bovine liver) by microwave-assisted wet digestion. The possibility of use O2 and H2O2 as auxiliary reagents for digestion using diluted HNO3. In this purpose, this work was divided in three steps: (i) investigation of the use of digestion vessel with O2 pressure to promote the regeneration of HNO3 allowing to use diluted HNO3 solutions; (ii) study of the influence of microwave radiation in the HNO3 regeneration process; and, (iii) evaluation of the use of an UV radiation emission lamp for sample digestion using diluted HNO3 with O2 and H2O2 as auxiliary reagents. Digestion efficiency, for all investigated parameters, was evaluated by the determination of residual carbon content (RCC) in final digests. Metals determination was performed by inductively coupled plasma optical emission spectrometry (ICP OES) and inductively coupled plasma mass spectrometry (ICP-MS). In the first step, the influence of O2 in the regeneration process was studied, by modifying the inert atmosphere of digestion vessel with O2 and Ar. Results obtained with the modified atmosphere were compared with those obtained without modification, only with the atmospheric air inside the vessel (without pressurization with O2 or inert gas previous to digestion). It was observed that by changing the internal atmosphere, with the addition of O2, it was possible to obtain the same digestion efficiency using diluted HNO3 solutions, in comparison with the efficiency obtained using concentrated acid. In addition, the possibility of using H2O2 was also investigated. Results similar to those obtained using O2 pressure were obtained using H2O2, allowing an efficient digestion using diluted HNO3 solutions. For higher H2O2 amounts, as well as for higher O2 pressure, residual acidity was higher, which was attributed to the participation of both reagents in the regeneration process of HNO3. With regard to the influence of microwave radiation in the regeneration process of HNO3 different experiments were performed: the forced air ventilation through the external vessel walls during the heating program; thermographic images were obtained; and, the study of the interaction of microwave radiation with gaseous phase into the reaction vessel. Taking into account the results obtained from these experiments, it was observed that despite to the temperature gradient at the beginning of the heating program, probably, the microwave radiation can promote a kinetic effect on the regeneration process in the gaseous phase. Finally, an UV radiation emission lamp was used for digestion of potato starch, imipramine hydrochloride and milk powder. It was observed that UV radiation allowed high digestion efficiency, even without using acid, probably by promoting the formation of oxidizing species. The results obtained from this work showed the suitability of using diluted HNO3 solutions for digestion of biological samples. Moreover, by understanding and exploring the aspects related to the reactions which occur during digestion, concerning the regeneration process of HNO3, it was possible to use less severe conditions, with the economy of reagents and reduction of residues, in agreement to the green chemistry recommendations.